Gott im Leid. Transformationen der Theodizee bei Simone Weil und Dorothee Sölle - König, Katrin (Dorothee Sölles Theologie: Anregungen - Anfänge - Beziehungen)

'(-)bio(-)' als Bestandteil von Lebensmittelmarkennamen: Eine kognitiv-grammatische Untersuchung zur Komposition von Markennamen - Dübbert, Alexander (Zeitschrift für Wortbildung)
'bioZENTRALE', 'Bio Liebe', 'dmBio', 'Kölln Bio' etc.: Bei der Benamung von Lebensmittelmarken wird die Komponente '(-)bio(-)' angesichts der Verbreitung biologisch hergestellter Produkte häufig eingesetzt. Marken verwenden sie mal in Präposition und mal in Postposition, mal gebunden und mal frei. Dieser Beitrag untersucht diese unterschiedlichen Verwendungen aus einer kognitiv-grammatischen Perspektive anhand eines Korpus aus aktuellen Lebensmittelmarkennamen. Ziel ist es, die Arten der Komposition zu systematisieren. Als Ausgangspunkt dienen die in der linguistischen Forschung bisher üblichen Klassifizierungen von 'bio-' als initiales Konfix sowie 'bio' als Kürzung. Die Analyse zeigt, dass die Komponente '(-)bio(-)' überwiegend als gebundene oder ungebundene spezifizierende Erst- oder auch Zweiteinheit in regulären Konfix-Komposita und kompositumähnlichen Bildungen, die als Markennamen eingesetzt werden, gebraucht wird. Seltener fungiert die Komponente selbst als Profildeterminante. Die Komponente '(-)bio(-)' wird demzufolge zur Bildung von Markennamen variabler gebraucht, als durch die Einordnung von bio- als vornehmlich linke, gebundene Einheit in Komposita bislang angenommen wurde.
Keywords: Markennamen; Konfix; bio; Kognitive Grammatik

K-Pop Demon Hunters: Selbstakzeptanz ohne Solidarität - Althoff, Sebastian (Zeitschrift für Medienwissenschaft, ZfM Online, GAAAP_ The Blog)

TFLN channel waveguides of rib and strip type: Properties of guided modes - Hammer, Manfred; Khan, Shahriar; Taheri, Behnood; Farheen, Henna; Förstner, Jens (Optics Continuum)
Straight dielectric waveguide channels made from slabs of thin-film lithium niobate (TFLN), or lithium niobate on insulator (LNOI), are investigated in the linear regime, for channels of rib and strip type with common trapezoidal cross sections, in Z-cut and X-cut samples at varying on-chip orientation. We clarify the theoretical basis for the waveguides with potentially non-diagonal core permittivity. Symmetry classes can be distinguished that differ in their consequences for potential modal degeneracy and polarization conversion. Our rigorous numerical analysis by means of a finite-element solver takes the anisotropy of the lithium niobate cores rigorously into account. We discuss extensive data for effective indices, polarization properties, and hybridization of guided modes, in single- and multimode channels. Scans over the waveguide width and orientation as primary parameters are complemented by a series of illustrations of vectorial mode profiles. These turn out to be essentially complex in cases of X-cut channels at non-crystal-axis-aligned orientations.
Keywords: tet_topic_waveguide

Interaction- or Material-Centred Implementation of Teacher Professional Development: a Comparison of Teachers’ Competence Development and Potential Lesson Planning Lehrkräftefortbildung interaktions- oder materialzentriert implementieren: Ein Vergleich hinsichtlich der Kompetenzentwicklung sowie der potentiellen Unterrichtsplanung von Lehrkräften - Richter, Alix; Bruns, Julia; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Abstract Teacher professional development (TPD) is a crucial support mechanism for mathematics teachers. Strategies for implementing TPD include disseminating educative curriculum materials or conducting TPD courses. However, it remains unclear whether different implementations of the same TPD support mathematics teachers in distinct ways. This study investigated two implementations of the TPD EmMa-FS which focuses early mathematics education (EME) for German vocational school (VS) teachers who instruct prospective early childhood (EC) educators. One group of teachers received an in-person TPD course along with educative curriculum materials ( n PM = 26), whereas the other received only the educative curriculum materials ( n M = 15). The effects on VS teachers’ beliefs and knowledge concerning EME were examined using a t -test and repeated measures ANOVA. To assess how teachers in the different implementation groups made use of the TPD in their lesson planning, participants submitted hypothetical lesson sequences on early numeracy, which were analysed for instructional quality, covered content, and the visible implementation of the provided educative curriculum materials using qualitative content analysis. The results indicated that both TPD implementations positively affected VS teachers’ knowledge related to EME but not their beliefs. While the instructional quality of the lesson sequences varied across both groups, participants who received the TPD course appeared to use the educative curriculum materials more often and to cover more content.

Mathematik mit Kindern ausgehend von Spiel- und Routinesituationen in der Kindertagesstätte erkunden? - Bruns, Julia; Mette, Tessa (Frühe Bildung)
Zusammenfassung: Frühe mathematische Bildung, die ihren Ausgangspunkt in den (Spiel-)Situationen der Kindertagesstätte nimmt, kann breite mathematische Erfahrungen ermöglichen, wenn die (Spiel-)Situationen entsprechende Möglichkeiten bieten. Erste Studien weisen darauf hin, dass in diesen Situationen verschiedene mathematische Inhalte angesprochen werden können. Allerdings konzentrieren sich bisherige Studien auf ausgewählte Kontexte oder Inhaltsbereiche. Diese Studie zielt daher auf eine vertiefte Analyse der Gelegenheiten für mathematische Erfahrungen, die in verschiedenen (Spiel-)Situationen im Alltag der Kindertagesstätte entstehen können. Dazu wurde eine videobasierte Beobachtungsstudie mittels einer Action-Kamera in einer Kindertagesstätte durchgeführt. Die Ergebnisse zeigen, dass eine Vielfalt von mathematischen Inhalten in (Spiel-)Situationen in der Kindertagesstätte beobachtet werden kann, einzelne Inhalte jedoch nur in formellen Lernsituationen auftreten.

Failure behavior prediction for resistance spot-welded three-layered dissimilar joints with advanced high-strength steel - Olfert, Viktoria; Bähr, Philipp; Schuster, Lilia; Westhoff, Julia; Yang, Keke; Ibeski, Enes; Hein, David; Sommer, Silke; Meschut, Gerson (Journal of Manufacturing Processes)

Sharing the Fame but Taking the Blame: When Declaring a Single Person Responsible Solves a Free Rider Problem - Li, Xinyu; Schnedler, Wendelin (Management Science)
Teams are formed because input from different people is needed. Providing incentives to team members, however, can be difficult. According to received wisdom, declaring all members responsible fails because real responsibility for team output “diffuses.” But why? Also, why and when does formally declaring one member “responsible” mean that this member can be attributed real responsibility? We offer a model that answers these questions. We identify when jointly declaring a team responsible results in reputation free riding. We show that declaring one person responsible can overcome this problem but only if all other team members are protected from being sanctioned. This paper was accepted by Dorothea Kübler, behavioral economics and decision analysis.

Tagungen zur Logik - Peckhaus, Volker (: „… eine so innige Verwebung sowohl sachlicher wie auch persönlicher Art.“ Zu den Tagungen am Mathematischen Forschungsinstitut Oberwolfach, 1945–1960)

Abschlussbericht: Sprachliche Bildung im Kontext von Mehrsprachigkeit. Impulse zur Gestaltung eines mehrsprachigen Kita-Alltags in den städtischen Kindertageseinrichtungen in Köln - Albers, Timm; Meusel, Sarah

Essen nach Zahlen - Die Quantifizierung von Ernährung im Alltag - Schloots, Franziska Margarete (Virtuelles Essen- Interdisziplinäre Perspektiven auf Ernährungspraktiken im digitalen Zeitalter)
Keywords: Selbstvermessung; Wearables; Diet Tracking; Quantifizierung

Brownian motion conditioned to spend limited time outside a bounded interval – an extreme example of entropic repulsion - Aurzada, Frank; Kolb, Martin; Schickentanz, Dominic T. (Bernoulli)

Program Feature-Based Benchmarking for Fuzz Testing - Miao, Miao; Kummita, Sriteja; Bodden, Eric; Wei, Shiyi (Proceedings of the ACM on Software Engineering)
Fuzzing is a powerful software testing technique renowned for its effectiveness in identifying software vulnerabilities. Traditional fuzzing evaluations typically focus on overall fuzzer performance across a set of target programs, yet few benchmarks consider how fine-grained program features influence fuzzing effectiveness. To bridge this gap, we introduce FeatureBench, a novel benchmark designed to generate programs with configurable, fine-grained program features to enhance fuzzing evaluations. We reviewed 25 recent grey-box fuzzing studies, extracting 7 program features related to control-flow and data-flow that can impact fuzzer performance. Using these features, we generated a benchmark consisting of 153 programs controlled by 10 fine-grained configurable parameters. We evaluated 11 fuzzers using this benchmark, with each fuzzer representing either distinct claimed improvements or serving as a widely used baseline in fuzzing evaluations. The results indicate that fuzzer performance varies significantly based on the program features and their strengths, highlighting the importance of incorporating program characteristics into fuzzing evaluations.

Species Knowledge About a UNESCO Natural World Heritage Site and the Importance of Connectedness with Nature - Puppe, Ricardo; Schmäing, Till (Heritage)
Species knowledge of local animal species is of great importance for one’s own environmental awareness and is a major component for managing present and future crises in education for sustainable development. For this reason, this study is the first to survey the species knowledge of visitors to the UNESCO Natural World Heritage Site the Wadden Sea of the North Sea, which is the largest mudflat area in the world. In this context, the self-assessment of the respondents and the extent of their connectedness with nature are also examined. To answer the research questions, a questionnaire survey was carried out to determine the species knowledge and degree of connectedness with nature. For data analysis, various statistical methods such as t-tests and correlation analyses were used. The results show that the 126 visitors to the Wadden Sea Visitor Centre have a rather low level of species knowledge. In this regard, the European Herring Gull is the only very well-known species among the respondents. In addition, a further construct was investigated in the form of connectedness with nature, between which a significant positive correlation was found with species knowledge.

Topology-optimized silicon nitride coupler for integrated single-photon emitters - Farheen, Henna; Chen, Yuheng; Chen, Peigang; Kryvobok, Artem; Peana, Samuel; Senichev, Alexander; Shalaev, Vladimir M.; Boltasseva, Alexandra; Förstner, Jens; Kildishev, Alexander V. (Photonic Computing: From Materials and Devices to Systems and Applications II)
We present a topology-optimized silicon nitride (Si3N4) coupler designed to enhance the coupling efficiency between integrated single-photon emitters and photonic waveguide modes. By leveraging inverse design techniques, we optimize the coupler’s geometry to maximize power transfer while maintaining fabrication feasibility by improving mode overlap and directional emission, addressing the challenge of low coupling efficiency caused by size mismatch and material incompatibility. Simulations demonstrate a substantial enhancement in photon extraction and waveguide coupling. This approach can be extended to other photonic devices, offering a versatile framework for improving quantum light-matter interactions in integrated photonics.
Keywords: tet_topic_waveguide

From demand to action: Analysing building emissions and refurbishment scenarios towards climate neutrality - Kirschbaum, Julia; Divkovic, Denis; Meschede, Henning (Applied Energy)

Sustainable finance down-to-earth? Insights from the German regional economy - Knoll, Lisa; Klüh, Ulrich; Naji, Ilias; Rossmann, Felix (Finance and Space)

Sustainable Finance und Soziologie - Knoll, Lisa (Sustainable Finance. Die Zukunft nachhaltigen Investierens – ein interdisziplinärer Ausblick)

Vom Muster in die Struktur: Ein Verfahrenskonzept der Wissenschaftskommunikation für die BBNE - Kiepe, Karina; Schlömer, Tobias (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Ab initio calculations of spin waves: A review of theoretical approaches and applications - Neugum, Michael; Schindlmayr, Arno (Materials)
Spin waves represent an important class of low-energy excitations in magnetic solids, which influence the thermodynamic properties and play a major role in technical applications, such as spintronics or magnetic data storage. Despite the enormous advances of ab initio simulations in materials science, quantitative calculations of spin-wave spectra still pose a significant challenge, because the collective nature of the spin dynamics requires an accurate treatment of the Coulomb interaction between the electrons. As a consequence, simple lattice models like the Heisenberg Hamiltonian are still widespread in practical investigations, but modern techniques like time-dependent density-functional theory or many-body perturbation theory also open a route to material-specific spin-wave calculations from first principles. Although both are in principle exact, actual implementations necessarily employ approximations for electronic exchange and correlation as well as additional numerical simplifications. In this review, we recapitulate the theoretical foundations of ab initio spin-wave calculations and analyze the common approximations that underlie present implementations. In addition, we survey the available results for spin-wave dispersions of various magnetic materials and compare the performance of different computational approaches. In this way, we provide an overview of the present state of the art and identify directions for further developments.